Single center real-world analysis of the use of iliac branched devices for aorto-iliac aneurysm repair - Rodrigues,Marta Romão (2021)
Abstract Introduction: Endovascular repair of aortic aneurysms is widely established. However, aorto-iliac aneurysms pose a challenge, specifically regarding distal sealing. A frequent approach is extending the iliac limb to the external iliac artery (EIA) with occlusion of the internal iliac artery (IIA), often with varying degree of pelvic ischemia causing significant morbidity. Iliac branched devices (IBD) allow for the creation of distal landing zones in the EIA and IIA, maintaining pelvic perfusion. We performed a descriptive analysis and outcome evaluation of IBD use in a single center patient cohort. Methods: An observational, descriptive, retrospective cohort analysis of all consecutive patients intended to treat with IBDs from Jan-2008 to Dec-2020 was performed. Technical success was defined as correct implantation of the IBD with confirmed patency of both EIA and IIA. We included all patients where at least one IBD was deployed, irrespective of additional procedures. Statistical analysis was performed using STATA 16, for Mac. Results: Of the initial 54 patients, 53 were included, (technical success 98,1%). Fifty-two were men (98.2%), mean age 73.5 years (SD 8.1). Mean aortic diameter was 56.4mm (SD 13.4), mean CIA aneurysm diameter 37.0mm (SD 12.7). A total of 60 IBD’s were performed (CookÆ Medical’s ZBIS device), of which 5 as part of complex aortic treatment with fenestrated endografts, 32 EVAR with unilateral IBD, 7 EVAR with bilateral IBD, 6 EVAR with unilateral IBD and contralateral extension to the EIA with embolization of the IIA and 3 isolated IBD (for type 1B endoleaks following EVAR or isolated iliac aneurysm). Peri-operative complications included acute kidney injury (AKI) (11,3% - 5/44), paraparesis and intestinal ischemia (1,9% each), one embolic intra-operatory stroke (1,9%) and one acute myocardial infarction (MI) (1,9%). Median follow-up was 9 months (IQR:16, 1-80months), during which 4,9% (2/42) developed type IB endoleaks, 4,9% (2/42) iliac aneurysm enlargement, 2,4% (1/42) limb kinking, 4,9% (2/42) limb occlusion, with a 7,14% (3/42) re-intervention rate. We found no association between limb patency and single, dual-antiplatelet treatment or anti-coagulation (p=0,6). There was no significative difference in AKI incidence between bilateral or unilateral IBD (irrespective of contra-lateral procedure). No in-hospital mortality was registered. There was one case of in-hospital death post-MI (1,9%), overall mortality 17% (9/53). Conclusion: In this cohort we found that the most common complication is AKI, apparently not directly related to the technique itself. Follow-up complications were few and mainly associated to loss of distal seal or limb occlusion, but implying a considerable re-intervention rate.